Principles of human joint replacement design and clinical application - Buechel, Fred; Pappas, Michael J. (Springer, 2015)
In its second extended edition it conveys to the reader the knowledge accumulated by the authors during their forty year effort on the development of replacement devices for the lower limb for the purpose of aiding the reader in their design and evaluation of joint replacement devices.